An at-home and electro-free COVID-19 rapid test based on colorimetric RT-LAMP - Diem Hong Tran; Hau Thi Tran; Trang Nguyen Minh Pham; Le Minh Bui; Huong Thi Thu Phung (Journal of Infection in Developing Countries)
Introduction: In the fight against virus-caused pandemics like COVID-19, diagnostic tests based on RT-qPCR are essential, but they are sometimes limited by their dependence on expensive, specialized equipment and skilled personnel. Consequently, an alternative nucleic acid detection technique that overcomes these restrictions, called loop-mediated isothermal amplification following reverse transcription (RT-LAMP), has been broadly investigated. Nevertheless, the developed RT-LAMP assays for SARS-CoV-2 detection still require laboratory devices and electrical power, limiting their widespread use as rapid home tests. This work developed a flexible RT-LAMP assay that gets beyond the drawbacks of the available isothermal LAMP-based SARS-CoV-2 detection, establishing a simple and effective at-home diagnostic tool for COVID-19.